'English is the Only Language Which I Speak': New Narratives in Reich's My Name Is (1967). Issue 3 (4th July 2019) - Pymm, John
Abstract : Reich's My Name Is (1967) has become more widely known through its recent commercial recording by Powerplant (2012), but scholarly discussion of the piece has been until now almost entirely absent, despite the piece having been through a number of versions. The archival materials housed at the Paul Sacher Stiftung offer new insight into the work's compositional journey, from a piece generated by the voices of its audience to an ensemble work consisting of the voices of the performers themselves. What emerges is a tangled narrative of Reich's views of language, speech, and identity, which materialise through the evolution of My Name Is . One moment stands out in particular in this narrative, a little-known German version of the piece, Mein Name Ist … (Portrait der Schola Cantorum, 1981), which is a parallel work to an English version produced for Reich's own ensemble, My Name Is: Ensemble Portrait . The Bayer Records recording of the German piece released in 1993 was subsequently deleted, and Reich's later comment, 'Forget this piece, I have', appears to forbid further scholarly investigation. This paper offers a close reading of the versions of My Name Is, opening up new perspectives on the composer's approach to using speech material, and in so doing reassessing the piece's significance.